Determinants of the Effectiveness of Risk Management Implementation with Organizational Culture as a Moderating Variable - Rinaldi Rinaldi; Sutrisno T; Yeney Widya Prihatiningtias (Journal of The Community Development in Asia, 2024)
Risk management is essential in both private and public sectors to ensure financial stability and maximize stakeholder value. Despite Indonesia's National Medium-Term Development Plan mandating risk management in public organizations like the Ministry of Public Works and Housing (Ministry of PUPR), its implementation has faced challenges, including bribery and incomplete projects. This study examines the effects of human resources, budget allocation, and regulations on risk management effectiveness, with organizational culture as a moderating variable. Using a survey-based quantitative approach, data from employees in Echelon II Work Units at the Ministry of PUPR was analyzed through Structural Equation Modeling (SEM) with Partial Least Square (PLS). The findings reveal that human resources, budget, and regulations positively impact risk management effectiveness. However, organizational culture plays a mixed role, enhancing the impact of regulations while weakening the budget's effect and not significantly amplifying human resources on risk management. The study concludes that optimizing risk management requires focusing on human resources, aligning organizational culture with regulations, and managing budget impacts carefully